Analysis of the conformation and thermal stability of the high-affinity IgE Fc receptor β chain polymorphic proteins*. Issue 7 (2nd July 2016) - Terada, Tomoyoshi; Takahashi, Teppei; Arikawa, Hajime; Era, Seiichi
Abstract : The high-affinity IgE Fc receptor (FcεRI) β chain acts as a signal amplifier through the immunoreceptor tyrosine-based activation motif in its C-terminal intracellular region. Polymorphisms in FcεRI β have been linked to atopy, asthma, and allergies. We investigated the secondary structure, conformation, and thermal stability of FcεRI β polymorphic (β-L172I, β-L174V, and β-E228G) proteins. Polymorphisms did not affect the secondary structure and conformation of FcεRI β. However, we calculated Gibbs free energy of unfolding (Δ G unf ) and significant differences were observed in Δ G unf values between the wild-type FcεRI β (β-WT) and β-E228G. These results suggested that β-E228G affected the thermal stability of FcεRI β. The role of β-E228G in biological functions and its involvement in allergic reactions have not yet been elucidated in detail; therefore, differences in the thermal stability of β-E228G may affect the function of FcεRI β. Graphical abstract: Significant differences were observed in Δ G unf values between FcεRI β-WT and β-E228G.